Comprehensive evaluation of the global research on Zingiberaceae (1943–2022): A bibliometric study - S. I. Abdelwahab; M. M.E. Taha; A. A. Mariod (Учёные записки Казанского университета: Серия Естественные науки)
Zingiberaceae has long been used medicinally, culinarily, and cosmetically, especially in tropical and subtropical regions. However, despite attracting substantial funding and research interest, they remain unexplored from a bibliometric perspective. Using the Scopus database, this study summarizes the global research output on Zingiberaceae from 1943 to 2022. The Scopus search resulted in 3589 Englishlanguage journal articles and conference proceedings. The bibliometric networks were visualized with the VOSviewer software. The analysis revealed that the most published author is J.K. Hwang affiliated with Yonsei University (South Korea), while the Chinese Academy of Sciences (China) holds the largest number of publications among the institutions. The works on Zingiberaceae cover multiple topics from 27 disciplines, with agricultural and biological sciences contributing the most (23.5 %). Other key research areas and subjects include ethnobotany, traditional knowledge, botanical and taxonomic studies, essential oils, pure chemicals, and individual species. India emerged as the most collaborative country, and S. Nayak from Siksha O Anusandhan University (India) stands out as the most collaborative researcher. The Journal of Ethnopharmacology leads in the publication and citation counts. The above results define the current status and future hotspots of the research on Zingiberaceae plants.